MORINGA LEAVES IMPROVE HYSTOPATOLOGY WHITE RATS HEPAR EXPERIENCED DIABETIC - Pidada, Ida Ayu Adhistania; Setiasih, Ni Luh Eka; Winaya, Ida Bagus Oka (Buletin Veteriner Udayana; Vol. 10 No. 1 Pebruari 2018DO - 10.24843/bulvet.2018.v10.i01.p08, 2018)
This study aims was to investigate the improvement of hepar histopathology experimental diabetic rats given moringa oleifera leaves ethanolic extract. 24 male white rats induced by a single dose STZ of 45mg/kg intraperitoneal to cause diabetes mellitus. After declared with diabetes disease, rats were divided into 6 groups consist of 1 a control group and a treatment group of 5 who were given ethanol extracts of leaves of the kelor, with a dose of 100, 200, 300, 400, and 500mg/kg, for 5 weeks. Rats then sacrificed and the hepar were taken for the histopathology preparations with Hematoxylin-Eosin staining (HE). Each preparation histopathology examined under a microscope in five visual fields at 400x magnification. The processed data is then analyzed statistically by test Non parametric Kruskal Wallis followed by Mann-Whitney test, when there is a significant difference (P<0.05). The results showed that the hepar has improved a result of the damage diabetes mellitus after given Moringa oleifera leaves ethanolic extract with a dose of 400 mg/kg.